An Evaluation of Lighting Design Performance in Cafes as Informal Learning Spaces - Muhammad Daffa Samudera; Asri Dinapradipta; Ima Defiana (Ikatan Peneliti Lingkungan Binaan Indonesia, 2026)
The proliferation of urban cafes has driven a shift in spatial function, with these venues increasingly used by students as informal learning environments rather than solely for socializing. This phenomenon demands a spatial quality that supports user comfort, particularly regarding lighting design. This study aims to evaluate the performance of natural and artificial lighting in cafes functioning as informal study spaces. A quantitative approach was employed by directly measuring illuminance levels, Correlated Color Temperature (CCT), and glare perception across two cafe case studies. The results indicate that during the daytime, the average illuminance in both cafes complies with the baseline SNI 6197:2020 standard for cafe spaces; however, only one cafe meets the recommended standard for learning environments, and light distribution remains uneven, leaving certain areas below the required threshold. At night, illuminance in one cafe fell below the standard for studying, whereas the other remained compliant. Regarding CCT, daytime lighting in both cafes demonstrated a neutral warm-white ambiance, transitioning to a warm tone at night. Furthermore, daytime glare perception varied between the two cafes, whereas nighttime glare remained consistently low in both cafes. These findings provide an empirical basis for formulating recommendations to improve lighting design in cafes utilized as informal learning spaces.